2010
DOI: 10.1194/jlr.r008730
|View full text |Cite
|
Sign up to set email alerts
|

Shedding new light on lipid biology with coherent anti-Stokes Raman scattering microscopy

Abstract: Despite the ubiquitous roles of lipids in biology, the detection of lipids has relied on invasive techniques and population measurements. The molecular profi les of the lipid-rich structures are evaluated by measurements of total lipid extracts with liquid or gas chromatography coupled to mass spectrometry ( 8 ). This approach is inexact because it measures lipid molecules from areas other than the structures of interest. Furthermore, spatial information, which is critical to understanding the function of lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
131
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(131 citation statements)
references
References 126 publications
0
131
0
Order By: Relevance
“…More detailed review articles can be found for a general overview [20-23, 42, 203], and in Pezacki et al [204] for biological applications and Le et al [205] for more specific applications relating to lipid research.…”
Section: Coherent Anti-stokes Raman Scattering (Cars)mentioning
confidence: 99%
“…More detailed review articles can be found for a general overview [20-23, 42, 203], and in Pezacki et al [204] for biological applications and Le et al [205] for more specific applications relating to lipid research.…”
Section: Coherent Anti-stokes Raman Scattering (Cars)mentioning
confidence: 99%
“…Liver lipid level measurement based on CARS signal intensity has been described in detail previously ( 24 ). Briefl y, after subtraction of nonresonant signal and signal arising from cellular membrane, the square root of resonant signal intensity yields a numerical value for the liver lipid level ( 25,26 ). The liver lipid level was normalized to 1 for wild-type, untreated mice and respectively for UPase1 -TG mice .…”
Section: Cars Microscopymentioning
confidence: 99%
“…CARS microscopy has already been used for imaging a number of delicate biological samples and processes, e.g. imaging of C-H stretching vibration present in the lipid bilayer of the cell membranes [101][102][103]. Two other Raman imaging techniques with great potential have evolved recently: Stimulated Raman scattering spectroscopy and Ultrafast Raman loss spectroscopy [104][105][106][107].…”
Section: Resonance Raman Spectroscopy Surface Enhanced Raman Spectromentioning
confidence: 99%